2022
DOI: 10.3390/antiox11071219
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-Assisted Aqueous Extraction of Chlorogenic Acid and Cynarin with the Impact of Inulin from Burdock (Arctium lappa L.) Roots

Abstract: The ultrasound-assisted aqueous extraction of chlorogenic acid (CGA) and cynarin with the impact of inulin from burdock (Arctium lappa L.) roots was investigated. Three extraction modes, ultrasound at 40 kHz/300 W (U-40), ultrasound at 120 kHz/300 W (U-120), and shaking at 120 rpm (S-120), were compared. The effects of process parameters on the extraction of polyphenols, CGA, cynarin, inulin, and antioxidant activity using U-40 were evaluated. In 10 min, 50 °C, and 1/30 (g/mL-water) of solid-to-liquid ratio, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Chen et al evaluated various ultrasound conditions for CGA extraction from burdock (Arctium lappa L.) roots. Their study demonstrated selective extraction of CGA and cynarin between frequencies of 40 kHz and 120 kHz [59].…”
Section: Functional Foods High In Chlorogenic Acidmentioning
confidence: 98%
“…Chen et al evaluated various ultrasound conditions for CGA extraction from burdock (Arctium lappa L.) roots. Their study demonstrated selective extraction of CGA and cynarin between frequencies of 40 kHz and 120 kHz [59].…”
Section: Functional Foods High In Chlorogenic Acidmentioning
confidence: 98%
“…The changes in antioxidant activity might have resulted from the changes in the content of functional ingredients after fermentation, such as the content of isoflavones and phenolic compounds, because the responses of Lp-BCRC10357 might vary when experiencing different environmental stresses. Chen et al (2022) reported that the antioxidant activity was substantially related to the contribution of the phenolic compounds [30]. Gupta et al (2018) indicated that the increase in antioxidant activity in okara after fermentation might be attributed to an increase in the content of phenolics [31].…”
Section: Antioxidant Activity Of the Fermented Productmentioning
confidence: 99%
“…Ultrasound-assisted extraction (UAE) is one of the non-traditional technologies that is most often employed to obtain enriched extracts in interesting analytes from natural matrices. This analytical technique uses the power of ultrasound to increase the extraction yield by generating cavities and localized hotspots that break the matrix's cell walls, thus favoring the transfer of the interesting compounds into the solvent [21,22]. Extraction yields can also be enhanced based on the polarity of the solvent used [23,24].…”
Section: Of 12mentioning
confidence: 99%